2009
DOI: 10.1021/ja9053306
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Contrast Agent Charge on Visualization of Articular Cartilage Using Computed Tomography: Exploiting Electrostatic Interactions for Improved Sensitivity

Abstract: The synthesis and evaluation of a new class of cationic iodinated contrast agents for the imaging of cartilage using computed tomography (CT) are described. In direct comparisons with anionic contrast agents, the cationic contrast agents afforded higher equilibrium concentrations in the articular cartilage of ex vivo rabbit femurs and thus greater imaging sensitivity. Variations in CT intensity across the sample reflected the inhomogeneous distribution of glycosaminoglycans in the tissue as confirmed by histol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
130
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

6
1

Authors

Journals

citations
Cited by 92 publications
(134 citation statements)
references
References 16 publications
2
130
0
Order By: Relevance
“…The second set was used for investigating how CA4+ chondron accumulation would affect the analysis conducted with lower resolution µCT systems. The CA4+ solutions were prepared as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…The second set was used for investigating how CA4+ chondron accumulation would affect the analysis conducted with lower resolution µCT systems. The CA4+ solutions were prepared as previously described [7].…”
Section: Methodsmentioning
confidence: 99%
“…Cationic contrast agents (especially CA4+), compared to anionic ones, demonstrate strong positive correlation to GAG content and reveal GAG distribution in articular cartilage even when used at low concentrations [5][6][7]. Successful application of these cationic contrast agents in ex vivo and in vivo studies [7,8] indicate significant research potential.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Three plugs were randomly therapies entering preclinical and clinical studies for the treatment of damaged cartilage. In 2009, we reported the synthesis of new cationic iodinated CT contrast agents for imaging articular cartilage that were designed on the basis of favorable electrostatic interactions between negatively charged glycosaminoglycans (GAGs) and the positively charged contrast agent (1). Use of these agents to image individual ex vivo rabbit femurs with x-ray CT has shown that the greater cationic charge on the agents yields higher CT attenuation.…”
Section: Imaging Protocol For Uptake Experimentsmentioning
confidence: 99%